Determinants of healthcare expenditures: evidence from Türkiye’s healthcare system - Diğer, Hülya; Çebi Karaaslan, Kübranur; Köstekçi, Ahmet; Göv, Abdullah (Frontiers in Public Health, 2025)
BackgroundThe lack of a mandatory referral system for service demand in Türkiye’s health system and the belief that unnecessary health expenditures are increasing constitute the basis of this study. This study aims to analyze the determinant role of individuals in health expenditures in Türkiye in two dimensions: household indicators and indicators for the head of the household, taking into account health expenditure policies.MethodsIn this study, the factors affecting households’ out-of-pocket health expenditures are tested with the help of binary probit regression analysis using the micro data set of the Turkish Statistical Institute 2022 Household Budget Survey.ResultsThe findings revealed no significant relationship between out-of-pocket health expenditures and variables such as gender, education level, employment status, private insurance ownership, alcohol and tobacco use, ease of access to a health center, receipt of monetary aid, or household size.ConclusionAccording to the results of the research, older individuals spend more on health expenditures. Expenditures increase in parallel with education expenditures and health expenditures decrease as income level increases.